2018
DOI: 10.1245/s10434-018-6502-x
|View full text |Cite|
|
Sign up to set email alerts
|

Rates of TP53 Mutation are Significantly Elevated in African American Patients with Gastric Cancer

Abstract: Significantly higher rates of TP53 mutations were identified among the African American patients with gastric adenocarcinoma. This is the first study to evaluate tumor genomic differences in a diverse population of patients with gastric adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
1
16
0
1
Order By: Relevance
“…In this study, we sought to gain a deeper understanding of the molecular features of gastric cancer in the AN population. Our analysis of a targeted 50 somatic gene mutation panel confirmed 60.6% of the patients had one or more gene mutations with the TP53 gene being the most frequently altered among AN patients, which was similar but lower in frequency, 36% when compared to other populations, 46-49% [13,[22][23][24]. Other genes that were commonly mutated in AN gastric cancer patients were PIK3CA, PTEN, KRAS, APC, and CTNN1B, which were comparable to the TCGA study (Table 3) [13].…”
Section: Discussionmentioning
confidence: 56%
“…In this study, we sought to gain a deeper understanding of the molecular features of gastric cancer in the AN population. Our analysis of a targeted 50 somatic gene mutation panel confirmed 60.6% of the patients had one or more gene mutations with the TP53 gene being the most frequently altered among AN patients, which was similar but lower in frequency, 36% when compared to other populations, 46-49% [13,[22][23][24]. Other genes that were commonly mutated in AN gastric cancer patients were PIK3CA, PTEN, KRAS, APC, and CTNN1B, which were comparable to the TCGA study (Table 3) [13].…”
Section: Discussionmentioning
confidence: 56%
“…Poor outcomes could be attributed to environmental and genetic factors. It has been reported that AA patients tend to have higher rates of TP53 mutation, a universally accepted aggressive tumor marker, attributing to about 89% patients, in comparison to 40% in the Caucasian population [23]. Other contributing factors could be high prevalence of Helicobacter pylori infections seen in AA, and presentation at an older age [16,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…In previously published studies, the presence of TP53 gene mutation was not proved to be an independent prognostic factor for patients with advanced GCs[ 1 , 12 ], or it was correlated with a shorter survival[ 13 , 14 ]. Our study confirmed the longer survival of wt cases, compared to those with TP53 gene mutation, especially in patients without lymph node metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The TP53 mutation rate was proved to be dependent by various parameters, including geographic characteristics known to be induced by interactions between Helicobacter pylori infection and other environmental, molecular and genetic factors[ 13 , 15 , 16 ]. In our study, which included Romanian patients, the mutation rate was 33.83%, similar to American Caucasian (40%) and Hispanic patients (43%), whereas Asian and African American patients, similar to patients in Bangladesh, proved to have significantly elevated mutations rates of 56%, 89%, and 73%, respectively[ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%